Defining the disease liability of variants in the cystic fibrosis transmembrane conductance regulator gene - Sosnay, Patrick R; Siklosi, Karen R; Van Goor, Fredrick; Kaniecki, Kyle; Yu, Haihui; Sharma, Neeraj; Ramalho, Anabela S; Amaral, Margarida D; Dorfman, Ruslan; Zielenski, Julian; Masica, David L; Karchin, Rachel; et al. (Nature genetics, 2013)
Garry Cutting and colleagues report a comprehensive functional and clinical analysis of CFTR variants reported in cystic fibrosis. They determine that 128 of 160 CFTR variants with an allele frequency of >0.01% are causal for disease. Allelic heterogeneity in disease-causing genes presents a substantial challenge to the translation of genomic variation into clinical practice. Few of the almost 2,000 variants in the cystic fibrosis transmembrane conductance regulator gene CFTR have empirical evidence that they cause cystic fibrosis. To address this gap, we collected both genotype and phenotype data for 39,696 individuals with cystic fibrosis in registries and clinics in North America and Europe. In these individuals, 159 CFTR variants had an allele frequency of ł0.01%. These variants were evaluated for both clinical severity and functional consequence, with 127 (80%) meeting both clinical and functional criteria consistent with disease. Assessment of disease penetrance in 2,188 fathers of individuals with cystic fibrosis enabled assignment of 12 of the remaining 32 variants as neutral, whereas the other 20 variants remained of indeterminate effect. This study illustrates that sourcing data directly from well-phenotyped subjects can address the gap in our ability to interpret clinically relevant genomic variation.